Orientasi Strategis di Era Digital: Mengintegrasikan Adopsi AI dan Literasi Digital pada Ratuna 21 Menuju Keunggulan Kompetitif, UKM Kuliner di Kota Bandung, Indonesia - Susi Nurohimah; Alma Aulia Siffa; Maliha Rizka Humaira; Megha Sakova (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study analyzes the influence of AI Adoption (X1), Digital Literacy (X2), and Strategic Orientation (X3) on Competitive Advantage (Y) in the RaTuna21 culinary MSME in Bandung City. Using a quantitative approach through a survey of 35 consumer respondents, analyzed with SPSS-assisted regression. The results indicate that partially, all three variables have a positive and significant effect on competitive advantage, with AI Adoption as the most dominant factor (Beta = 0.713). However, when tested simultaneously, only AI Adoption remains significant (Beta = 0.494), while Digital Literacy and Strategic Orientation lose their influence due to overlap between variables. The simultaneous model is able to explain 54.7% of the variation in Competitive Advantage, thus confirming that AI adoption is the most dominant strategic resource in shaping the competitive advantage of culinary MSMEs in the digital era according to the Resource-Based View perspective.